2003
DOI: 10.1046/j.1460-9568.2003.02663.x
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptors on microglial cells: functional expression in acute brain slices and modulation of microglial activation in vitro

Abstract: Microglial cells are the pathologic sensors in the brain. ATP released from damaged cells is a candidate for signalling neural injury to microglia. Moreover, ATP is an extracellular messenger for propagating astrocyte activity in the form of Ca2+ waves. To test for the functional expression of purinoreceptors in microglial cells we employed the patch-clamp technique in acute slices of adult mouse brain. ATP triggered a nonselective cationic and a K+ current. Pharmacological screening with purinergic ligands in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
171
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(186 citation statements)
references
References 42 publications
15
171
0
Order By: Relevance
“…Previously, we and others have reported that adenine di-and triphosphate nucleotides, the endogenous ligands for P2 receptors, exert anti-inflammatory effects in microglia [3,4]; however, the specific P2 receptors involved in these actions are not yet clear. The P2Y14 receptor, previously called GPR105 (an orphan G-protein coupled receptor), has only recently been identified as a member of the purinergic receptor family [1]; hence, comparatively little is known about its function in any cell type.…”
Section: Introductionmentioning
confidence: 92%
“…Previously, we and others have reported that adenine di-and triphosphate nucleotides, the endogenous ligands for P2 receptors, exert anti-inflammatory effects in microglia [3,4]; however, the specific P2 receptors involved in these actions are not yet clear. The P2Y14 receptor, previously called GPR105 (an orphan G-protein coupled receptor), has only recently been identified as a member of the purinergic receptor family [1]; hence, comparatively little is known about its function in any cell type.…”
Section: Introductionmentioning
confidence: 92%
“…It has been reported that ramified microglia recruitment to the site of ischemia and hypoxia impairment is associated with cellular loss and P2X4-R are involved in cellular activation [19-21]. In this regard, the neuroprotective actions exerted by TNP-ATP and PPADS and the possible use of purinergic antagonist in the pharmacological treatment of oxygen/glucose deprivation have been considered [19-21,31]. Although P2X4 expression and inflammation after hypoxia-ischemia in the rat brain have been investigated after intraperitoneally injection of minocycline [22], the use of selected P2X4 antagonists to suppress AMC activation and associated inflammation in the postnatal brain after hypoxia has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence to suggest that ATP is involved in microglial activation specifically in the ramified phenotype in the adult brain [24,25,31]. On the other hand, the role of ATP in AMC activation especially the mechanisms in hypoxia have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible modes of ATP release: (1) damaged neurons are depolarized by the elevated extracellular K + due to impairment of the Na + -K + pump. ATP passively flows out along the electrochemical gradient through membrane channels of glial cells [23] or from the presynaptic vesicles exocytotically [35] ; (2) organelles release ATP from astroglia in a Ca 2+ -independent manner via P2X 7 R channels [25,36] ; and (3) P2X 7 Rs on activated amoeboid microglia and reactive microglia amplify the ATP signal and trigger ATP release through an autocrine process [37,38] . In short, cerebral ischemia results in a sustained progressive elevation of ATP levels in the penumbra [22,23] .…”
Section: Leading To Cell Deathmentioning
confidence: 99%